Formulation of a Yield Surface for Sand Based on the Elastic Threshold Strain - Sang Inn Woo (Advances in Civil Engineering)
The present study proposes a rigorous expression of a yield function for sand based on the linear elastic threshold strain concept and empirical expression for the maximum shear modulus. The new yield function was calibrated for Toyoura sand. The calibration results show that the proposed yield surfaces are nonlinear curves that depend on the void ratio of sand in the p′-q plane, whereas the linear lines have been adopted in the bounding surface modeling of sand. This study also found that elliptic yield surfaces are the best fitted with the proposed yield surface and they can be used as alternatives to the proposed yield surface under the undrained shearing where the void ratio (or density) of sand is fixed.